2015
DOI: 10.1016/j.nmd.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of alternative alglucosidase alfa regimens in Pompe disease

Abstract: Emerging phenotypes in long-term survivors with Pompe disease on standard enzyme replacement therapy (ERT) (alglucosidase alfa 20 mg/kg/2 weeks) can include patients with worsening motor function. Whether higher doses of ERT improve skeletal function in these patients has not been systematically studied. This exploratory, randomized, open-label, 52-week study examined the safety and efficacy of 2 ERT regimens of alglucosidase alfa (20 mg/kg/week or 40 mg/kg/2 weeks) in 13 patients with Pompe disease and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 20 publications
(22 reference statements)
4
68
0
Order By: Relevance
“…Therefore, we directly compared the efficacy of intensive ERT with AAV2/8-LSPhGAA gene transfer at the established 12 low dose. GAA-KO mice were assigned (both male and female; Figure 1A; Table 1) to receive either a weekly injection of rhGAA for intensive ERT 15 (20 mg/kg/week; n = 10) or a single injection of AAV2/8-LSPhGAA for low-dose gene therapy (8 × 10 11 vg/kg; n = 10). The primary endpoints included GAA activity and glycogen content in the tissues and anti-GAA antibody formation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we directly compared the efficacy of intensive ERT with AAV2/8-LSPhGAA gene transfer at the established 12 low dose. GAA-KO mice were assigned (both male and female; Figure 1A; Table 1) to receive either a weekly injection of rhGAA for intensive ERT 15 (20 mg/kg/week; n = 10) or a single injection of AAV2/8-LSPhGAA for low-dose gene therapy (8 × 10 11 vg/kg; n = 10). The primary endpoints included GAA activity and glycogen content in the tissues and anti-GAA antibody formation.…”
Section: Resultsmentioning
confidence: 99%
“…Early initiation of rhGAA infusion after diagnosis through NBS improves the outcomes of IOPD, but muscle weakness, ptosis, and speech disorders still occurred [7], [17]. An increase in the dosage or frequency of rhGAA infusion appears to provide some benefits to these patients but is not sufficient to prevent residual symptoms [7], [22], [23]. In the current study, we demonstrated that albuterol speeded the climb of patients and selectively improved muscle function and movement quality, but we could not prove its benefit in the 6MWT consistently nor its significant benefit in other measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Pompe disease (PD), a rare autosomal recessive condition also known as glycogen storage disease type II, is caused by deficiency of the lysosomal enzyme acid α‐glucosidase (GAA). This enzyme deficiency results in glycogen accumulation in various organs, primarily muscle tissue . The clinical severity of the disease depends on the degree of enzyme deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The most severe form with predominantly cardiac involvement is classic infantile‐onset PD (IOPD) with an estimated frequency of 1:138 000 . Patients with IOPD typically have marked hypertrophic cardiomyopathy, respiratory distress, feeding problems, motor delay, failure to thrive, muscle weakness, and hypotonia . IOPD is rapidly progressive and used to be considered uniformly lethal with the vast majority of patients dying in the first year due to cardio‐respiratory failure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation